An empirical investigation into alarming signals ignored by the U.S. multi-brand retailer J. Crew Incorporation during COVID-19 pandemic - Ganga Bhavani; Reena Agrawal; Suhan Mendon; Cristi Spulbăr; Ramona Birau (Journal of Risk and Financial Management, 2021)
This study investigated the financial signals that have been ignored or have failed to be controlled by J. Crew Inc. from 2013 until 2019. Exploratory research is carried out with the help of secondary data which was collected from the downloaded formal documents submitted by J. Crew Inc. to the Securities Exchange Commission (SEC). Researchers analyzed these documents and prepared statements on vertical income statement, vertical balance sheet, horizontal income statement, horizontal balance sheet, trend analysis of income statement, and trend analysis of balance sheet, as well as ratio analysis on liquidity, long-term solvency, profitability, and turnover ratios with the help of excel. This paper has identified total of 15 alarming signs that companies either ignored, could not control, or did not act with alertness towards to stop the business being taken out of hands. In this research paper, the establishment of J. Crew Inc. was presented in four sections: Crew Retail Stores, Crew Factory Stores, Crew Mercantile Stores, and Crew Madewell Stores. The results of this study show that it was not the COVID-19 pandemic that pushed this retail giant into bankruptcy, but numerous reasons and financial turbulences. J. Crew's financial performance gave plenty of alarming signals that the showed the company was not on track, but these were ignored by the company. Right from net profit, operating expenses, total revenue, goodwill, return on assets, liquidity, and solvency, all 15 indicators were not meeting the industry ideal standard for a continuous period of 5 years. Whether or not the organization can rebuild and contend in a post-pandemic world, is not yet clear.
Keywords: 330; Crew Retail Stores; Crew Factory Stores; Crew Mercantile Stores; Crew Madewell Stores; financial performance; financial analysis